FEATURES OF APPLICATION OF FILTERS KALMAN-BJUSI IN ORIENTATION AND NAVIGATION COMPLEXES - A. S. Benkafo; A. A. Lobaty (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
On the basis of an optimum filtration theory the analysis of methodical errors which are possible at application an optimum estimation algorithm of stochastic system phase co-ordinates is carried out. Research of these errors by modelling of a concrete example is carried out.